Acute esophageal necrosis complicated by refractory stricture formation. Issue 4 (1st March 2021) - Sandhu, Sunny; Wang, Timothy; Prajapati, Devang
Abstract: Acute esophageal necrosis (AEN) is a rare presentation of severe esophageal injury. The optimal long‐term management of complications related to AEN, particularly stricture formation, are not well defined. We report a case of AEN in a patient who presented with diabetic ketoacidosis (DKA) and had dysphagia due to refractory stricture formation after mucosal healing occurred. A 62‐year‐old male with diabetes mellitus presented with altered mental status. He was admitted for hypovolemic shock secondary to DKA and treated with vasopressors, fluid resuscitation, and insulin. After resolution of DKA, he reported persistent dysphagia. Upper endoscopy showed circumferential black mucosal discoloration throughout the entire esophagus that spared the gastroesophageal junction. He was diagnosed with AEN and was continued on a proton pump inhibitor and sucralfate with improvement in symptoms. Repeat endoscopy 4 weeks later showed a 10‐cm benign‐appearing stricture in the mid esophagus. He underwent dilation with temporary symptomatic relief; however, recurrence in symptoms has thus far necessitated a total of 10 repeat upper endoscopies, including repeat dilations along with local steroid injection therapy. AEN is a rare presentation of severe esophageal injury and is typically associated with severe hemodynamic compromise. Although most cases resolve with supportive care and mucosal healing, there is little information regarding prognosis and optimal management of complications, such as refractory esophageal strictures. We describe a case of AEN complicated by refractory symptomatic esophageal stricture despite several dilations and intralesional steroid injections and discuss our approach to treatment. Abstract : Acute esophageal necrosis (AEN) is a rare presentation of severe esophageal injury. The optimal long‐term management of complications related to AEN, particularly stricture formation, are not well defined. We report a case of AEN in a patient who presented with diabetic ketoacidosis who had dysphagia due to refractory stricture formation after mucosal healing occurred, and discuss our approach to treatment.